Hubungan Antara Komunikasi Kelompok Guru dengan Motivasi Belajar Murid pada Masa PTMT - Azhar Panji Pratama; Anne Maryani (UNISBA Press, 2023)
Abstract. The Covid 19 outbreak has enveloped Indonesia since 2020, of course this has an impact on all aspects of life in Indonesia, especially in the education aspect. Face-to-face education must now be replaced by online learning since PPKM was implemented. This policy reduces students' learning motivation because they are not familiar with the online learning process. Since the COVID-19 pandemic has begun to subside, the government has implemented a PTMT policy or Limited Face-to-face Learning at the SMA/SMK equivalent education level. As a communicator in the communication process that occurs in learning at school, a teacher must convey messages properly to the communicant or his students. The PTMT policy makes the distribution of material provided by the teacher less evenly distributed, because this policy is a hybrid which makes students divided into two groups, some are learning face-to-face and some are learning online. This makes the teacher have to conduct group discussions to find solutions to these problems. The research entitled